Influence of Soy-enriched Cookies on Bone Mineral Density in Perimenopausal Women - Munir, Maira; Khanum, Farah; Nudrat; Rasheed, Yusra; Jafar, Muntaha; Sara; Aslam, Anam; Arshad, Misbah (An Overview of Disease and Health Research Vol. 2, 2025)
Background: Isoflavones are abundant in soy and other legumes, have established estrogenic properties, and had impressive biological effects in preclinical models. Isoflavones have been suggested as alternatives to hormone replacement therapy. Objectives: This study evaluates the influence of soy-enriched cookies on bone mineral density in perimenopausal women. Methodology: A total of 36 women with perimenopausal older than 40 years were enrolled for the 8 weeks of study, and participants of the study were allocated into two groups, 18 participants in each group. Group G0 was the control group with no supplementation, and group G1 was the treatment group with 40g soy flour cookies. The participants were selected from the Orthopedic ward of Jinnah Hospital, Lahore. The 40g soy cookies were given to the participants on a daily basis for 8 weeks. The study parameters such as Vitamin D, Calcium, Phosphorus and BMD levels were measured at the start and end of the study. Results: The mean age of participants enrolled in this study was 43.042±3.79 years in G0, and in G1 it was 42.45 ±4.45. The mean BMI was 24.2±3.10 and 22.50±2.50 kgm-2 in both groups, respectively after treatment, with no statistical association. There was a significant change observed in Vitamin D levels with values of 23.82±4.373 and 26.50±4.50, pre and post-treatment respectively. Calcium levels improved significantly, rising from 11.52±3.01 to 12.00±2.85 with significant association (p-value less than 0.05). On the other hand, Phosphorus levels also increased from 2.62 ± 0.75 to 3.00 ± 0.80 mg/dL. At the same time, BMD levels significantly (P<0.05) improved in the treatment group from 0.727±0.09 to 0.800±0.1 with significant p-value. Conclusion: In conclusion, the study demonstrated that soy-enriched cookies significantly improve Vitamin D, calcium, phosphorus levels and bone mineral density in perimenopausal women. These findings suggest that incorporating soy flour cookies into the diet could be an effective strategy for enhancing bone health and mineral metabolism in this population.